Initiatives to improve prescribing efficiency for drugs to treat Parkinson's disease in Croatia: influence and future directions. (June 2012) - Brkicic, Ljiljana Sovic; Godman, Brian; Voncina, Luka; Sovic, Slavica; Relja, Maja
Parkinson's disease (PD) is the second most common neurological disease affecting older adults. Consequently, this disease should be a focus among payers, with increasing utilization of newer premium-priced patent-protected add-on therapies to stabilize or even improve motor function over time. However, expenditure can be moderated by reforms. Consequently, there is a need to assess the influence of these reforms on the prescribing efficiency for drugs to treat PD in Croatia before proposing additional measures. Prescribing efficiency is defined as increasing the use of add-on therapies for similar expenditure. An observational retrospective study of the Croatian Institute for Health Insurance database of drugs to treat patients with PD in Croatia from 2000 to 2010 was carried out, with utilization measured in defined daily doses (defined as the average maintenance dose of a drug when used in its major indication in adults). The study years were chosen to reflect recent reforms. Only reimbursed expenditure is measured from a health insurance perspective. Utilization of drugs to treat PD increased by 218% between 2000 and 2010. Reimbursed expenditure increased by 360%, principally driven by increasing utilization of premium-priced patent-protected add-on therapies, including ropinirole and pramipexole. However, following recent reforms, reducing expenditure/defined daily dose for the different drugs, as well as overall expenditure, stabilized reimbursed expenditure between 2005 and 2010. Treatment of PD is complex, and add-on therapies are needed to improve care. Reimbursed expenditure should now fall following stabilization, despite increasing volumes, as successive add-on therapies lose their patents, further increasing prescribing efficiency.